ANALYSIS OF DIGITAL MARKETING, PRODUCT QUALITY, AND CUSTOMER TRUST STUDIES ON CONSUMER SATISFACTION ON TIKTOK SHOP - Jentoro Wicaksono; Edwin Zusrony; Robby Andika Kusumajaya (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study examines the impact of trust, the quality of merchandise, and various online marketing methods on customer satisfaction of TikTok Shop users in Semarang. Focused on the 18-25 year old Gen Z population who frequently use the TikTok Shop, the study sample consisted of 50 participants. The researchers used survey instruments consisting of Likert-type scales, and then afterward carried out multiple regression analysis with SmartPLS 4.0 software. The results of the study hypothesize that online promotions, merchandise quality, and trust as independent and composite variables will positively influence customer satisfaction. This study enhances existing social commerce and online customer behavior knowledge while providing TikTok Shop owners with tactical suggestions on developing better community-driven marketing, enhancing product quality, and building trust to increase customer loyalty.